Using Graphic Organizer to Improve the Students’ Reading Comprehension Achievement - Prihatin Puji Astuti (Universitas Pamulang, 2020)
This study investigated the use of a graphic organizer reading strategy in improving the students’ reading comprehension achievement. It was aimed to find out to what extend the improvement of the students reading comprehension after being treated using the graphic organizer strategy. This research also wanted to check the differences in the result between the class which used the graphic organizer and the class which did not apply a specific reading strategy. This study was conducted at the grade 11 students of SMK Sasmita Jaya Tangerang Selatan. This research administered cluster random sampling in taking samples and decided two classes as the same samples. One class was treated using a graphic organizer and the other class was not treated using any specific kind of strategy or conventional strategy. The method of this research was quantitative research under quasi-experimental research. A quasi-experimental design was used to know the result after specific treatment was applied. After collecting the data, then it was analyzed using SPSS. Based on the result of the data analysis, it was found that applying the Graphic Organizer reading strategy in reading lessons could improve students’ reading comprehension achievement.